DAMPAK PERILAKU MENYONTEK TERHADAP PERKEMBANGAN MORAL PESERTA DIDIK DI KELAS XI IPS - Yanti, Novi; Sulistyarini, Sulistyarini; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2024)
This study aims to find out how the impact of cheating behavior on the moral development of students in class XI IPS SMA Negeri 2 Simpang Hilir Kayong Utara Regency. The research method used in this study is a descriptive method with a qualitative research form. Sources of data in this study were Civics subject teachers, BK subject teachers and class XI IPS students. Data collection techniqques, while the data collections tools used were observation guides, interview guides and documentation. The analysis in this study was presented in a qualitative descriptive manner using 5 informants. The results of this study indicate that (1 The causes of cheating behavior are internal and external factors. (2 a form of cheating behavior arried out by students in class is making small notes by writing poinst from the material, looking at textbooks and storing textbooks under the table, looking friends answers, and cooperate with other friends to fill in the answers. (3 The teachers efforts in dealing with cheating behavior are by providing habituation or requiring students to keep their bags in front of the class before the repetition begins, giving directions not to commit cheating behavior and informing about sanctions caught cheating. (4 The impact of cheating behavior on the moral development of students is that students will be lazy, habitually lie or be dishonest do not want to try and unsure of their own answers.